Vapor induced phase separation towards anion-/near-infrared-responsive pore channels for switchable anti-fouling membranes. Issue 18 (27th April 2020) - Wei, Ran; Guo, Jiabei; Jin, Lunqiang; He, Chao; Xie, Yi; Zhang, Xiang; Zhao, Weifeng; Zhao, Changsheng
Abstract : Development of anion-/near-infrared-responsive and anti-fouling membranes fabricated through vapor induced phase separation based on poly(ionic liquid) nanoparticles. Abstract : As an important type of smart membrane, stimuli-responsive membranes with switchable separation capability and permeability are urgently needed for developing advanced filtration membranes. In this study, smart membranes with anion-/near-infrared (NIR)-responsive and improved anti-fouling properties were fabricated by introducing poly(ionic liquid) (PIL) modified Fe3 O4 nanoparticles on the surfaces and pore channels of polyethersulfone membranes through the vapor induced phase separation (VIPS) method. Thanks to the anion-/NIR-responsiveness of the nanoparticles, adjustable surface wettability and pore sizes of the membranes were obtained. The fluxes of the membranes were well-controlled along with adjusting the sizes of the nanoparticles via anion-exchange and NIR irradiation. The switchable pore size was further demonstrated by the filtration of polyethylene glycol (PEG)-800 and PEG-2000. In addition, the wettability and zeta-potential of the membrane surfaces could be adjusted by exchanging the counteranions of the immobilized PIL nanoparticles, which endowed the membranes with robust anti-fouling abilities toward biological contaminants like bovine serum albumin when changing the counteranions from hydrophilic to hydrophobic. After the counteranion exchange desorption, the intelligent membranes were then self-cleaned.